Influence of infection on malaria‐specific antibody dynamics in a cohort exposed to intense malaria transmission in northern Uganda. (1st May 2013) - Proietti, C.; Verra, F.; Bretscher, M. T.; Stone, W.; Kanoi, B. N.; Balikagala, B.; Egwang, T. G.; Corran, P.; Ronca, R.; Arcà, B.; Riley, E. M.; Crisanti, A.; et al.
Summary The role of submicroscopic infections in modulating malaria antibody responses is poorly understood and requires longitudinal studies. A cohort of 249 children ≤5 years of age, 126 children between 6 and 10 years and 134 adults ≥20 years was recruited in an area of intense malaria transmission in Apac, Uganda and treated with artemether/lumefantrine at enrolment. Parasite carriage was determined at enrolment and after 6 and 16 weeks using microscopy and PCR. Antibody prevalence and titres to circumsporozoite protein, apical membrane antigen‐1 (AMA‐1), merozoite surface protein‐1 (MSP‐119), merozoite surface protein‐2 (MSP‐2) and Anopheles gambiae salivary gland protein 6 (gSG6) were determined by ELISA. Plasmodium falciparum infections were detected in 38·1% (194/509) of the individuals by microscopy and in 57·1% (284/493) of the individuals by PCR at enrolment. Antibody prevalence and titre against AMA‐1, MSP‐119, MSP‐2 and gSG6 were related to concurrent (sub‐)microscopic parasitaemia. Responses were stable in children who were continuously infected with malaria parasites but declined in children who were never parasitaemic during the study or were not re‐infected after treatment. These findings indicate that continued malaria infections are required to maintain antibody titres in an area of intense malaria transmission.